PENGARUH STRATEGI BRANDING TERHADAP KECEPATAN PERTUMBUHAN PERUSAHAAN STARTUP - Adhika Prawira; Fakhrun Nisa; Raden Sultan; Yusak Yonatan (Journal of Technology and Engineering, 2026)
Technology has advanced significantly across various sectors, particularly in today's era of digitalization. Nearly everyone has become highly dependent on technology, especially smartphones. Over a 24-hour period, individuals may spend up to 18 hours using their smartphones, a duration comparable to the time devoted to other daily activities. This phenomenon occurs because most of the goods, services, and information people require are readily accessible through their smartphones. Consequently, contemporary businesses have increasingly shifted toward digital platforms. To support business growth and introduce products or services to the public, companies must implement marketing strategies. Marketing strategies can generally be categorized into two approaches: short-term and long-term strategies. In the short term, companies may adopt tactics designed to generate rapid increases in traffic and visibility, often referred to as a "hit-and-run" approach. In contrast, long-term strategies require companies to gradually and consistently establish the value of their products or services over time, thereby fostering stronger emotional connections between customers and the offerings provided. Therefore, branding strategies play a crucial role in developing and maintaining customer emotional attachment to a company.